1976
DOI: 10.1021/bi00668a008
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification of bacterial luciferase with ethoxyformic anhydride: evidence for an essential histidyl residue

Abstract: Bacterial luciferase is a heteropolymeric protein (alphabeta) that catalyses the conversion of chemical energy to light by oxidation of a reduced flavin mononucleotide and a long chain aliphatic aldehyde. Elucidation of the specific amino acid residues involved in the enzymatic reaction is essential for understanding the mechanisms of the bioluminescent reaction. Luciferase has been found to be inactivated by ethoxyformic anhydride with a second-order rate constant of 146 M-1 min-1 at pH 6.1 and 0 degrees C wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 52 publications
7
52
0
Order By: Relevance
“…The His-modifying agent DEPC is commonly used to assess possible involvement of His residues in native or recombinant ion channel or transporter function and, in particular, their involvement in pH sensitivity. DEPC carboxyethylates the proton-titratable imidazole group of His in a pH-sensitive reaction (7,29), and DEPC specificity for His modification has been claimed at pH 5.5-7.5 (3). We have shown that DEPC can reversibly inhibit AE2-mediated Cl Ϫ transport in Xenopus oocytes, in contrast to its irreversible inhibition of kAE1 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The His-modifying agent DEPC is commonly used to assess possible involvement of His residues in native or recombinant ion channel or transporter function and, in particular, their involvement in pH sensitivity. DEPC carboxyethylates the proton-titratable imidazole group of His in a pH-sensitive reaction (7,29), and DEPC specificity for His modification has been claimed at pH 5.5-7.5 (3). We have shown that DEPC can reversibly inhibit AE2-mediated Cl Ϫ transport in Xenopus oocytes, in contrast to its irreversible inhibition of kAE1 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…At higher concentrations of DEP, a second irreversible carbethoxylation may take place (step 2). Hydroxylamine will catalyze an opening of the dicarbethoxylated histidyl ring (step 3) tion process although generally very fast, sensitive, and complete (Burstein et al, 1974;Cousineau & Meighen, 1976) can be very slow (Miles & Kumagai, 1974;Wiejnans & Muller, 1982). Another explanation for the lack of complete decarbethoxylation by NH2OH is the possible irreversible carbethoxylation of the second nitrogen atom in the imidazole ring followed by an opening of the ring in the presence of NH2OH (see Fig.…”
Section: By Nhzohmentioning
confidence: 99%
“…Some specify binding of substrate, e.g. His in pyridoxamine phosphate oxidase (Tsuge and McCormick, 1977), and in a bacterial luciferase, where FMNH, is a cosubstrate (Cousineau and Meighen, 1976). In some instances, it is not clear what the role of a given residue may be, even when the proximity to flavin may contribute to observed fluorescence quenching, e.g.…”
Section: (C) Other C U Mmentioning
confidence: 99%